Institutional Performance of Mining Reclamation in Forest Areas of East Kalimantan - Rina Kristanti; Hariadi Kartodihardjo; Bramasto Nugroho; Irdika Mansur (Jurnal Manajemen Hutan Tropika, 2019)
The Indonesian Government accommodates the development of mining sector conducted in forest area based on Forestry Law Number 41/1999 by the scheme of Forest Leasehold License. Reclamation is required to remediate the degraded land caused by mining activity to restore forest structure and function. This study aimed to analyze the implementation of mining reclamation in East Kalimantan forest areas based on its institutional performance. This study is a descriptive qualitative study that implemented the institutional framework of Situation-Structure-Behavior-Performance. From the study, we found that there are 143,804.89 ha of forest area borrowed by 90 units of Forest Leasehold License for coal and mineral mining in East Kalimantan with reclamation progress reached 41.35% over the disturbed areas. Based on institutional performance analysis, it is identified that the challenges in mining reclamation in East Kalimantan forest areas related to regulation, low sanction enforcement, lack of budget, human resource and economic incentives, and the absence of low-cost technology for mining reclamation monitoring and evaluation. Therefore, development of proper regulations is urgently required to improve stakeholder behavior while enhancement of human resource, technology, and law enforcement are also urgent to improve institutional performance of mining reclamation.Keywords: